Ways to neutralize the country-of-origin effect in the emerging market firms international branding1 - Witek-Hajduk Marzanna Katarzyna; Grudecka Anna (International Journal of Management and Economics, 2023)
The purpose of this paper is to examine the ways in which to neutralize the country-of-origin (COO) effect (COE) in the emerging market of firms’ international branding.